A mixed methods investigation on British expatriate assignment success - Hardy, Claire (2011)
Psychological research on expatriation has been dominated by North American researchers, and expatriation models have been tested using predominantly US employee samples. This dominance may bias our understanding of expatriation and influence the practice of expatriate assignments within organisations. This thesis addresses the need for European expatriation research, and investigates expatriate assignment success from a British employee perspective. A sequential mixed-methods design was used to examine whether existing knowledge on predictors for successful expatriate assignments can be generalised to British samples. The first phase of the research was a qualitative exploration of factors that contribute to expatriate assignment success from the British employee perspective. Four focus groups were conducted with formerly expatriated British employees (n=14). An inductive thematic analysis was conducted on the focus group transcripts, which resulted in nine themes highlighting the importance of individual, organisational, and contextual-level variables. Moreover, the analysis highlighted an important outcome variable that has been largely ignored in previous research: whether or not the employee would go on another expatriate assignment. From the results of phase one, an initial model of British expatriate assignment success was hypothesised. Phase two involved the practical application of the variable considered most important in contributing to expatriate assignment success from study one: personality. A new expatriate assignment personality instrument was developed in phase two using a sample of British employees (n=402). The third phase of the research combined the results of the previous two phases, and employed an embedded mixed-methods design to further investigate British expatriate assignment success. Data (n=155) was collected using an online questionnaire sent to currently expatriated (n=91) and formerly expatriated British employees (n=45), as well as their accompanying partners (n=19 expatriate/partner dyads). The quantitative element explored the influence of several individual, organisational, and contextual variables on various expatriate assignment success outcome measures. Qualitative data was also collected through open-ended questions placed within the questionnaire to help explain and support the quantitative results, and identify potential areas for future research. Finally, the newly developed personality instrument from phase two was further examined for psychometric robustness. Overall, this thesis presents an initial model of British expatriate assignment success and a new personality instrument for British expatriate selection and assessment contexts. The theoretical and practical implications of these results are discussed together with suggestions for future research.